Planning Of The Coiled Tubing Gas Lift Method To Overcome Esp Start-Up Failure In Well Ppa-003 - Kurniawan Triyo Widodo (Cerdika: Jurnal Ilmiah Indonesia, 2025)
The PPA-003 well in the Puspa Structure, Jambi Field, faces technical challenges due to the start-up failure of the Electric Submersible Pump (ESP) caused by the presence of heavy complex fluids. This condition hampers the initial production process and reduces the operational efficiency of the well. This study aims to design a nitrogen (N?) injection method through coiled tubing applied alongside the ESP start-up as a solution to lift the heavy complex fluids and enable the well to flow stably. The proposed approach involves using coiled tubing to inject N? into the well during the start-up process, thereby reducing the pressure gradient inside the tubing and lowering the total dynamic head (TDH) that must be supported by the ESP pump. Once the well flows and stable flow is achieved, the coiled tubing will be removed, and the operation will continue solely with ESP support. This study includes a technical analysis of the causes of start-up failure, N? injection design, ESP performance evaluation, and well flow simulation. The research results indicate that this method is effective in overcoming start-up obstacles by reducing the density of the heavy mud (kill fluid), allowing the ESP to operate within the equipment's operational limits. The recommendations from this study are expected to serve as a reference for addressing similar challenges in other wells, particularly in the Jambi Field area.